On the performance of asymmetric SIM‐based RF/FSO system with MIMO DF relaying. Issue 5 (28th February 2018) - Singhal, Neha; Bansal, Ankur; Kumar, Ashwni
Abstract: In this paper, we consider the asymmetric dual‐hop radio frequency (RF) and free‐space optical (FSO) wireless communication system with a decode‐and‐forward–based multiple‐input–multiple‐output relay over the Nakagami‐ m /Generalized‐ K ( K G ) distribution. The K G distribution is a generic statistical model, which has been used for a wide range of atmospheric turbulence–induced fading in FSO communication. The coefficients of the RF hop are considered to be independent and nonidentically distributed with the Nakagami‐ m distribution, and the coefficients of FSO hop are considered to be independent and identically distributed. We also consider the path loss and misalignment error effect in FSO hop. We derive the approximate closed‐form expression of the symbol error probability and outage probability in terms of the Meijer G function for the considered mixed decode‐and‐forward RF/FSO system. The closed‐form expressions of the conditional symbol error probability and outage probability are also derived for the considered system while taking into account the effect of a misalignment error. We have also analyzed the considered system for high signal‐to‐noise ratio conditions. In addition, the diversity order of the considered system is also obtained analytically. Abstract : We consider an asymmetric dual‐hop radio frequency and free‐space optical wireless communication system with a decode‐and‐forward based multiple‐input‐multiple‐output relay. The error performance and outage performance are analyzed while considering the effect of path‐loss with both negligible and significant misalignment error condition over FSO hop. Further, we perform the asymptotic analysis of the considered system in order to obtain the diversity order analytically.